Analysis on the hazardous jarosite added concrete - Mehra, Priyansha (2020)
This paper attempts to propose a new method for re-use of jarosite in concrete. Jarosite added concrete was studied for different mechanical and durability properties. The experiments were performed in the laboratory and statistical analysis was done using JMP software to predict the models for different test results by the method of least squares. The models were reduced to equations which depend on water-cement ratio, number of days and jarosite replacement ratios. The strength (compressive and flexural tensile) and abrasion resistance was found increasing, however the depth of water penetration and amount of water absorption was reduced with the increased jarosite content in concrete. Chloride Ion Penetration after 28 and 56 days of immersion was calculated and satisfactory results was observed.